Epidemiology and clinical presentation of feline cataracts in france: A retrospective study of 268 cases. (6th March 2018) - Guyonnet, Alexandre; Donzel, Elise; Bourguet, Aurélie; Chahory, Sabine
Abstract: Objective: To describe the epidemiology and the clinical presentation of cataracts in a population of cats in France. Procedures: A review of medical records of cats presented to the Ophthalmology Unit of the National Veterinary School of Alfort between January 2010 and June 2017 was carried out to identify cats affected by cataracts. The signalment of affected cats, medical history, etiology of cataract, age of onset, stage of development, location of opacities, and concurrent ocular lesions were evaluated. Results: Of 2054 cats which were presented to the Ophthalmology Unit of the National Veterinary School of Alfort during the study period, 268 (383 eyes) were diagnosed with a cataract (13%; CI [11.3‐14.7]). The median age of all cats affected by cataract was 9.5 years (range: 0.1‐18.6 years). Eighteen breeds were represented. The recorded causes of cataract were uveitis (35.8%), congenital (15.7%), aging (10.8%), presumed hereditary (8.2%), trauma (7.8%), lens luxation (3.3%), glaucoma (1.5%) and diabetes mellitus (0.4%). In 16.4% of the cases, the etiology could not be determined. The domestic short‐hair was significantly overrepresented in cats with uveitis‐related cataract ( P < .001). The most common ocular lesions associated with cataracts were lens subluxation or luxation (17.8%), glaucoma (14.9%), and retinal detachment (4.4%). Lens subluxation/luxation and glaucoma were also significantly associated with uveitis‐related cataract ( P < .001). Conclusions: In a French population of referred cats, 13% were affected by cataract. The main causes identified were anterior uveitis, congenital, and aging. Lens subluxation/luxation and glaucoma were associated with uveitis‐related cataract.